1940
DOI: 10.1021/ja01861a029
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Separation of Isomeric Hexenes by Fractional Distillation

Abstract: Attempted Separation of Hexenes by Distillation 795 of magnitude of the number of plates required, but consideration of the holdup and the 30 to 1 reflux ratio actually used in these distillations would certainly increase the estimates considerably.9Consideration of Holdup and Reflux Ratio.-All the above computations are on the assumption that reflux was nearly total and that holdup was zero so that the conclusions are for maximum sharpness of separation and minimum plates required. No statement of the holdup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1941
1941
1968
1968

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Goldwasser and Taylor (24) report extensive studies on the hexenes. Their methods of analyses are such that considerable doubt is cast on their results (59,87). An example of their results showed that alumina at 398°C.…”
Section: + Hydrogen Chloridementioning
confidence: 99%
See 1 more Smart Citation
“…Goldwasser and Taylor (24) report extensive studies on the hexenes. Their methods of analyses are such that considerable doubt is cast on their results (59,87). An example of their results showed that alumina at 398°C.…”
Section: + Hydrogen Chloridementioning
confidence: 99%
“…Further, Rose (59) showed by calculation and Whitmore et al (87) by experimental evidence that it is impossible to separate many of the isomeric products of n-hexene by present methods of fractional distillation. Literature reports that are based on questionable analytical methods are reviewed in this paper only in the absence of data obtained by more credible methods.…”
mentioning
confidence: 93%
“…Stedman column and that the perforated plate column has a higher maximum reflux rate or capacity. Comparison with the helix-packed type of column (8) shows that the perforated plate column has a lower average holdup per theoretical plate per 100 ml. of reflux per minute.…”
Section: Discussion Of Datamentioning
confidence: 99%
“…from the data given in Tables I and II and Bragg's data (I) on the Stedman type packing which has been included for purposes of comparison. Similar data on columns of the helix-packed type (3,7,8) could not be calculated from the information given in the literature. Data on the Bruun column (2) were also omitted, since the operating holdup was not given for a specified reflux rate.…”
Section: Constructionmentioning
confidence: 94%
“…Although the problem of devising such a column has been a common one throughout the history of organic chemistry, it has only been in the past few years that successful investigations have been carried out in this field. Of the several recent comprehensive articles concerning laboratory fractionation columns, those of Whitmore et al (11) and Podbielniak (8) are the most important, since these two articles contain a critical discussion of all recently developed fractionating columns.…”
mentioning
confidence: 99%